VIABILITY OF THE MINI-CUTTING TECHNIQUE IN THE PRODUCTION OF Drimys brasiliensis Miers SEEDLINGS - Maggioni, Renata de Almeida; Romanini Netto, Emilio; Latoh, Leandro Porto; Koehler, Henrique Soares; Zuffellato-Ribas, Katia Christina (Floresta, 2020)
Drimys brasiliensis, popularly known as cataia or casca-d’anta, is a tree species native to the Atlantic Forest and belonging to the family Winteraceae. Due to its seeds have dormancy due to embryonic immaturity, the present work aimed to evaluate the viability of the mini-cutting technique in D. brasiliensis in different seasons of collection of the propagules. Mini-cuttings from seedlings sprouts previously produced by conventional cutting were collected at six different times (December/2015, February/2016, April/2016, June/2016, August/2016 and October/2016), made 6-8 cm long, with bevel cut at the base and rectum at the apex, keeping two leaves with their area halved. The experiment was carried out in a completely randomized design with 4 replicates and 14 mini-cuttings per experimental unit. The mini-cuttings were planted in tubes with substrate containing vermiculite and carbonized rice husk (1:1) and kept in a heated greenhouse. After 120 days, the percentage of rooted mini-cuttings, number of roots per mini-cuttings, length of the three largest roots by mini-cuttings, percentage of mini-cuttings with callus, live, dead, with shoots and leaves that maintained their original leaves were evaluated. Rooting percentages of mini-cuttings were greater than 75% regardless of the season of the year in which the propagules were collected. The adventitious root formation of D. brasiliensis occurs indirectly, from the callus tissue formed at the base of the mini-cuttings. The mini-cuttings technique is recommended for the production of seedlings of the species, at any seasons of the year.